2016
DOI: 10.1007/s10875-016-0284-3
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health and Related Quality of Life in Patients with Congenital Agammaglobulinemia in the Northern Region of the UK

Abstract: IntroductionPatients with congenital agammaglobulinemia, characterized by a defect in B lymphocyte differentiation causing B alymphocytosis, require life-long IgG replacement. There is scant literature regarding the effectiveness of IgG treatment at preventing mucosal (particularly sinopulmonary tract) infection and whether current management adequately restores “normal” health and quality of life (QoL). We aimed to document infective episodes pre- and post-commencing IgG replacement, determine any change in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…For protection from lung complications, the IVIg doses should be increased in order to maintain serum IgG level >800 mg/dL and antimicrobial prophylaxis with regular chest physiotherapy should be started . A recent study on respiratory health and related quality of life in patients with congenital agammaglobulinemia showed a significant burden of respiratory disease on a patient's life …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For protection from lung complications, the IVIg doses should be increased in order to maintain serum IgG level >800 mg/dL and antimicrobial prophylaxis with regular chest physiotherapy should be started . A recent study on respiratory health and related quality of life in patients with congenital agammaglobulinemia showed a significant burden of respiratory disease on a patient's life …”
Section: Discussionmentioning
confidence: 99%
“…18 A recent study on respiratory health and related quality of life in patients with congenital agammaglobulinemia showed a significant burden of respiratory disease on a patient's life. 28 From 26 different families, 26 different mutations were detected. Mutations that we identified in our patients had a similar distribution pattern to the mutations in the BTKbase.…”
Section: Discussionmentioning
confidence: 99%
“…Bryan et al . , in their survey of 15 patients with agammaglobinaemia from the North of England, suggested that there may well be a significant impact on patients' respiratory and overall quality of life. Larger studies are required to understand more fully the overall burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…An important question not addressed here is whether the observed radiological evidence of bronchiectasis and the poorer lung function corresponds to deterioration in patients' quality of life. Bryan et al [26], in their survey of 15 patients with agammaglobinaemia from the North of England, suggested that there may well be a significant impact on patients' respiratory and overall quality of life. Larger studies are required to understand more fully the overall burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…With an adequate immunoglobulin therapy, the rate of pneumonias is reduced by more than 10% [14] and lies within the range of 0.00-0.10 pneumonias per treatment year [13,37]. However, approximately 50% of patients might experience deterioration in their respiratory status while receiving immunoglobulin therapy [38]. The rate of infectious episodes during immunoglobulin therapy seems to be agerelated, since there is a threefold increased risk for infections in adult patients compared with pediatric patients (2.12 vs. 0.74 infections/patient/year) [38].…”
Section: Pulmonary Infectionsmentioning
confidence: 99%